Endogenous Effort Norms in Hierarchical Firms - Jan Tichem (Tinbergen Institute, 2013)
This paper studies how a three-layer hierarchical firm (principal-supervisor-agent) optimally creates effort norms for its employees. The key assumption is that effort norms are affected by the example of superiors. In equilibrium, norms are eroded as one moves down the hierarchy. The reason is that, because exerting effort is costly, the supervisor only partially complies with the principal's example, and thereby transmits a lower norm to the agent. The principal optimally responds to norm erosion by setting a higher example to begin with. In equilibrium, norm erosion gives rise to three inefficiencies: the principal works too hard, the supervisor's norm is too high, and the agent's norm is too low. To reduce these inefficiencies, firms should keep the extent of hierarchy to a minimum, promote employees with the strongest sensitivity to social norms, and distort man agerial spans of control.
Keywords: D23; M50; M51; 330; delayering; hierarchy; leading by example; norms; promotion; span of control